Novel Persian Gulf Aminated Alginate Derivatives from Sargassum Bovaneum: Synthesis and Characterization - Khodayar, Shokouh; Shushizadeh, Mohammad R.; Tahanpesar, Elham; Makhmalzadeh, Behzad Sharif; Sanaeishoar, Haleh (Letters in Organic Chemistry, 2023)
Aims: The aim of the study was to extract and characterize alginate from a new source, conduct synthesis and characterization of novel aminated alginate derivatives, make a comparison of physicochemical properties of extracted sodium alginate with its aminated derivatives, and investigate the effect of diamines chain length on physicochemical properties of newly synthesized derivatives. Background: Alginate is a natural biopolymer found in marine brown seaweeds. Alginate is widely used in the industry due to its features, such as gelling ability, biocompatibility, biodegradability, hydrophilicity, and non-toxicity. Alginate has two types of functional groups, free hydroxyl and carboxyl groups, which can be modified. Methods: In this study, sodium alginate was extracted from sargassum boveanum in basic media and characterized by physical and spectral properties. In order to prepare alginate precursors with clickable groups for hydrogel cross-linking application, extracted sodium alginate was further treated with two different diamines, diaminoheptane (DAH) and diaminopropane (DAP), in the presence of 1-ethyl-3- (3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) to form amide linkages on the alginate backbone and synthesise aminated derivatives. The products were characterized by techniques, such as FTIR, 1HNMR, TGA, XRD, and elemental analysis. Results: The average molar weight and the intrinsic viscosity of alginate from Sargassum bovaneum with a yield of 24.38% were 41.53 kDa and 0.9 dL/g 105 cps (2.5% C). Results showed that as the alginate concentration increased, the flow rate decreased with a mild slope. Conclusion: Elemental analysis (CHNS) of alginate derivatives indicated the percent of amine groups to be increased after amination reaction in comparison to corresponding alginates. The thermal analysis results indicate that the thermal stability of the sodium alginate is better than graft copolymers. Synthetic derivatives showed no particular sensitivity to environmental stimuli, such as temperature and pH changes.
Keywords: Alginate